Successful management of chronic eosinophilic pneumonia triggered by immune checkpoint inhibitor: a case report and literature review - Suzuki, Yasuhito; Saito, Junpei; Kubota, Satoshi; Ikeda, Masakazu; Rikimaru, Mami; Yamada, Ryuki; Kumanaka, Takahiro; Tanaka, Ryutaro; Kazama, Kentaro; Saito, Koshi; Harigane, Rina; Sato, Riko; et al. (Frontiers in Immunology, 2025)
Immune checkpoint inhibitors (ICIs) enhance antitumor immunity by blocking inhibitory immune signals, but can lead to immune-related adverse events (irAEs). Therefore, effective management of irAEs is crucial during ICI therapy. We report the case of a 50-year-old man who was referred to our department due to cough and abnormal chest shadows. He was diagnosed with hypopharyngeal cancer, and underwent chemoradiotherapy, resulting in complete remission. However, metastatic tumors were detected, and partial lung resection was performed. After one-year, new metastatic tumors and pleural dissemination were identified. Therefore, treatment with pembrolizumab was initiated. After the treatment with pembrolizumab, chest imaging revealed ground-glass opacity (GGO). Laboratory tests showed elevated eosinophils, and fractional exhaled nitric oxide (FeNO). The findings of bronchoscopy revealed eosinophilic infiltration and intraluminal fibrosis, consistent with chronic eosinophilic pneumonia (EP). Based on these findings, he was diagnosed with pembrolizumab-induced chronic EP. Pembrolizumab was temporarily discontinued, and oral corticosteroids (OCS) were initiated. After the treatment of OCS, his symptoms and GGO were dramatically improved. Subsequently, pembrolizumab was resumed, and the hypopharyngeal cancer remains stable without recurrence of EP. This report presents the first pembrolizumab-induced chronic EP during treatment for hypopharyngeal cancer. The chronic EP was effectively managed with systemic corticosteroid therapy. Furthermore, pembrolizumab was resumed with close monitoring of blood eosinophil counts and FeNO levels, without worsening of EP. The results of the current case suggest that ICI-induced chronic EP is manageable, and in cases where ICI therapy exhibits significant efficacy against cancer, its treatment may be continued with careful monitoring of these parameters.